The semantics of language in Eugène Ionesco’s plays - Nicolaescu, Cristina (Swedish Journal of Romanian Studies, 2024)
The goal of this paper is to present the characteristics of Eugène Ionesco’s dramatic texts, a reason why the genre of avant-garde and theatre of the absurd are also considered, with a view to revealing their major ways of functioning. By pointing out the different dimensions of dramatic language, the emphasis is on those elements that differ from current oral and written language. Starting from the times of decadentism, a crisis of character can be noted in the theater around a type of individual who, as an alienated individual, cannot find his identity in a hostile surrounding world. One of the direct consequences of this crisis will be the impossibility of interpersonal communication, which will be best demonstrated with the concept and tenets of the theater of the absurd. In this context, the study of the theater of the 20th century is done from the perspective of cognitive semantics, as an autonomous level of language. The approach is organised around two notions: dramatic conventions and the actual language of the dramatic texts. The interpretative theory rooted in semantics is applied while analysing Ionesco’s short plays. The starting point is the linguistics of the text as described by Eugen Coşeriu. Capturing the meaning and the means by which it is constructed is one of the objectives in accord with the main principles of cognitive linguistics. The way of analysing the meaning in a text is given by the presence of some textual functions, as possibilities provided by language through relationships that the linguistic sign establishes in the discursive act. The specificity of the discourse comes from the combination of verbal and non-verbal elements, in order to highlight the playwright’s original style. The particularities of this type of language based on an ontological representation of the actional nature in human existence are also investigated. There are two dimensions recognisable in the language of literature: one is specific to the genre and the other one is particular, giving originality and uniqueness. The textual meaning in between these dimensions needs to be reconstructed from all their constituents identifiable at different levels of analysis. Ionesco distanced himself from the conventional and traditional theatre, finding a new formula for the dramatic genre in his own vision of what drama should be like. Ionesco’s dramatic work includes short plays and extensive plays in which the author expresses his adversity against totalitarian regimes. He is the representative of the theater of the absurd and anti-theater. The corpus for this research is composed mainly of the plays The Bald Soprano, The Lesson and The Chairs, the most representative plays for the avant-garde spirit, short plays on the theme of language emptied of meaning and non-communication. Language has an impact on thinking and the resulting actions, which relates it to the ontology of human existence. As dramatic language is preponderently structured on dialogical interactions (and less on monologues, soliloquies and asides), its essence can be revealed by decomposing and recomposing them, from the angle of the conventions specific to the dramatic genre. The analysis of the selected fragments from the corpus has the role to highlight their semantic features in terms of conceptual representations.